Transformational leadership and turnover intention : mediating role of overall job satisfaction / Azlinda Hakim Lokman Hakim and Hairunnisa Mohamad Ibrahim - Lokman Hakim, Azlinda Hakim; Mohamad Ibrahim, Hairunnisa (Faculty of Hotel Management and Tourism, Universiti Teknologi MARA, Selangor, Puncak Alam Campus, 2017)
Turnover is one of the most critical issue in hotel industry. Turnover in front office department may somehow affect the hotel’s service quality standard and operations that may jeopardize the hotel image and guest expectation. An effective leadership style implemented by the management plays an important role in monitoring and maintaining the service consistency. In hospitality industry, transformational leadership has seen to be the most suitable leadership style that can be implement by the leader. This research will be focusing on transformational leadership among front office employees in Malaysian hotels as independent variable, and overall job satisfaction as mediating variable; which may lead to turnover intention as the outcome variable. A judgmental sampling technique was employed in this study. A total of 250 questionnaires were distributed randomly to both front office employees and managers who are working in selected four and five-star Malaysian hotels. The results of this study showed that the mediating role of overall job satisfaction have significant relationship between transformational leadership and turnover intention. Careful consideration of the best leadership style implemented in the department will justify the level of overall job satisfaction and turnover intention among front office employee.